Atopic dermatitis and bone health: a systematic review. (12th October 2020) - Mukovozov, I.M.; Morra, D.E.; Giustini, D.; Tadrous, M.; Cheung, A.M.; Drucker, A.M.
Abstract: Atopic dermatitis (AD) is associated with systemic inflammation and systemic corticosteroid use which can lead to poor bone health. The aim of this systematic review is to investigate the relationship between AD and bone mineral density (BMD), osteoporosis and fractures. We searched Web of Science, Cochrane Database of Systematic Reviews, MEDLINE and Embase. Title, abstract and full‐text screening, and data extraction were done in duplicate. Quality appraisal was performed using the Agency for Healthcare Research and Quality Methodology Checklist (cross‐sectional studies) and Newcastle‐Ottawa Scale (cohort studies). We screened 3800 abstracts and included fifteen studies (twelve cross‐sectional, three cohort). In cross‐sectional studies, AD was associated with decreased BMD and increased fractures. In cross‐sectional studies and a cohort study, AD was associated with a higher prevalence of osteoporosis compared to controls. There was inconsistency across studies, with some finding no association. In a large cohort study, AD was associated with increased risk of fractures of the hip (HR: 1.06, 95% CI: 1.02 to 1.11), spine (HR: 1.14, 95% CI: 1.06 to 1.23) and wrist (HR: 1.06, 95% CI: 1.01 to 1.10), with further increased risk with more severe AD. Differences between studies precluded quantitative synthesis. There is some evidence supporting an association between AD and poor bone health. Research is needed to clarify this association, underlying mechanisms and develop strategies to improve bone health of individuals with AD.